Palbociclib plus endocrine therapy in HER2 negative, hormonal receptor‐positive, advanced breast cancer: A real‐world experience. Issue 6 (10th December 2018) - Pizzuti, Laura; Giordano, Antonio; Michelotti, Andrea; Mazzotta, Marco; Natoli, Clara; Gamucci, Teresa; De Angelis, Claudia; Landucci, Elisabetta; Diodati, Lucrezia; Iezzi, Laura; Mentuccia, Lucia; Fabbri, Agnese; et al.
Abstract: Data from 423 human epidermal growth factor receptor 2‐negative (HER2−), hormone receptor‐positive (HR+) advanced breast cancer (aBC) patients treated with palbociclib and endocrine therapy (ET) were provided by 35 Italian cancer centers and analyzed for treatment outcomes. Overall, 158 patients were treated in first line and 265 in second/later lines. We observed 19 complete responses and 112 partial responses. The overall response rate (ORR) was 31% (95% confidence interval [CI], 26.6–35.4) and clinical benefit was 52.7% (95% CI, 48–57.5). ORR was negatively affected by prior exposure to everolimus/exemestane ( p  = 0.002) and favorably influenced by early line‐treatment ( p  < 0.0001). At 6 months, median progression‐free survival was 12 months (95% CI, 8–16) and median overall survival was 24 months (95% CI, 17–30). More favorable outcomes were associated with palbociclib in early lines, no visceral metastases and no prior everolimus/exemestane. The main toxicity reported was neutropenia. Our results provide further support to the use of palbociclib with ET in HER2−, HR+ aBC. Differences in outcomes across patients subsets remain largely unexplained. Abstract : Data from 423 human epidermal growth factor receptor 2‐negative (HER2−), hormone receptor‐positive (HR+) advanced breast cancer (aBC) patients treated with palbociclib and endocrine therapy (ET) were provided by 35 Italian cancer centers and analyzed for treatment outcomes. Our results provide further support to the use of palbociclib with ET in HER2‐, HR+ aBC. Differences in outcomes across patients subsets remain largely unexplained.